Outreach programs to improve life circumstances and prevent further adverse developmental trajectories of at‐risk youth in OECD countries: A systematic review. Issue 4 (17th October 2022) - Filges, Trine; Dalgaard, Nina T.; Viinholt, Bjørn C. A.
Abstract: Background: At‐risk youth may be defined as a diverse group of young people in unstable life circumstances, who are currently experiencing or are at risk of developing one or more serious problems. At‐risk youth are often very unlikely to seek out help for themselves within the established venues, as their adverse developmental trajectories have installed a lack of trust in authorities such as child protection agencies and social workers. To help this population, a number of outreach programmes have been established seeking to help the young people on an ad hoc basis, meaning that the interventions are designed to fit the individual needs of each young person rather than as a one‐size‐fits‐all treatment model. The intervention in this review is targeted outreach work which may be (but does not have to be) multicomponent programmes in which outreach may be combined with other services. Objectives: The main objective of this review was to answer the following research questions: What are the effects of outreach programmes on problem/high‐risk behaviour of young people between 8 and 25 years of age living in OECD countries? Are they less likely to experience an adverse outcome such as school failure or drop‐out, runaway and homelessness, substance and/or alcohol abuse, unemployment, long‐term poverty, delinquency and more serious criminal behaviour? Search Methods: We identified relevant studies through electronic searches of bibliographic databases, governmental and grey literature repositories, hand search in specific targeted journals, citation tracking, and Internet search engines. The database searches were carried out in September 2020 and other resources were searched in October and November 2021. We searched to identify both published and unpublished literature, and reference lists of included studies and relevant reviews were searched. Selection Criteria: The intervention was targeted outreach work which may have been combined with other services. Young people between 8 and 25 years of age living in OECD countries, who either have experienced or is at‐risk of experiencing an adverse outcome were eligible. Our primary focus was on measures of problem/high‐risk behaviour and a secondary focus was on social and emotional outcomes. All study designs that used a well‐defined control group were eligible for inclusion. Studies that utilised qualitative approaches were not included. Data Collection and Analysis: The total number of potentially relevant studies constituted 17, 659 hits. A total of 16 studies (17 different interventions) met the inclusion criteria. Only five studies could be used in the data synthesis. Eight studies could not be used in the data synthesis as they were judged to have critical risk of bias and, in accordance with the protocol, were excluded from the meta‐analysis on the basis that they would be more likely to mislead than inform. Two studies (three interventions) did not provide enough information enabling us to calculate an effect size and standard error, and one study did not provide enough information to assess risk of bias. Meta‐analysis of all outcomes were conducted on each conceptual outcome separately. All analyses were inverse variance weighted using random effects statistical models incorporating both the sampling variance and between study variance components into the study level weights. Random effects weighted mean effect sizes were calculated using 95% confidence intervals. Too few studies were included to carry out any sensitivity analyses. Main Results: Four of the five studies used for meta analysis were from the USA and one was from Canada. The timespan in which included studies were carried out was 32 years, from 1985 to 2017; on average the intervention year was 2005. The average number of participants in the analysed interventions was 116, ranging from 30 to 346 and the average number of controls was 81, ranging from 32 to 321. At most, the results from two studies could be pooled in a single meta‐analysis. It was only possible to pool the outcomes drug (other than marijuana) use, marijuana use and alcohol use each at two different time points (one and 3 months follow up). At 1 month follow up the weighted averages varied between zero and 0.05 and at 3 months follow up between −0.17 and 0.07. None of them were statistically significant. In addition, a number of other outcomes were reported in a single study only. Authors' Conclusions: Overall, there were too few studies included in any of the meta‐analyses in order for us to draw any conclusion concerning the effectiveness of outreach. The vast majority of studies were undertaken in the USA. The dominance of the USA as the main country in which outreach interventions meeting our inclusion criteria have been evaluated using rigorous methods and within our specific parameters clearly limits the generalisability of the findings. None of the studies, however, was considered to be of overall high quality in our risk of bias assessment and the process of excluding studies with critical risk of bias from the meta‐analysis applied in this review left us with only five of a total of 16 possible studies to synthesise. Further, because too few studies reported results on the same type of outcome at most two studies could be combined in a particular meta‐analysis. Given the limited number of rigorous studies available from countries other than the USA, it would be natural to consider conducting a series of randomised controlled trials evaluating the effectiveness of outreach for at‐risk youth in countries outside the USA. The trial(s) should be designed, conducted and reported according to methodological criteria for rigour in respect of internal and external validity to achieve robust results and preferably reporting a larger number of outcomes.